Content and Style of Advice in Iran and Canada - Tavakoli, Mahin (Canadian Journal of Counselling and Psychotherapy, 2012)
The content and nature of nonprofessional advice in Iran, a hierarchical and collectivist culture, was compared to the same type of advice in Canada, an egalitarian and individualist culture. A researcher developed a questionnaire that consisted of 10 letters, each describing a writer’s problem and asking for advice. The responses of participants to those letters were content-analyzed, which showed how advice varies between the two cultures. Implications of findings for developing multicultural techniques of counselling and psychotherapy are discussed.